2018
DOI: 10.1044/2018_ajslp-odc11-17-0189
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing a Resilient Mindset in School-Aged Children Who Stutter

Abstract: Purpose To consider the rationale, methods, and potential benefits of nurturing the growth of resilience in school-aged children who stutter. Stuttering in childhood can have negative psychological consequences for some, including the development of a negative attitude toward their speech from a young age (Vanryckeghem, Brutten, & Hernandez, 2005) and possible co-occurring psychopathology in adolescence and adulthood, in particular, anxiety disorders (Blood, Blood, Maloney, Meyer, & Qualls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In addition, the role of parents is a key factor in modeling resilient responses to children and creating a resilience-rich environment. Some CWS may benefit from targeted support and build their own resilience to overcome the challenges about stuttering (19) .…”
Section: Studies On Resilience Social Support and Trait Anxiety Levelsmentioning
confidence: 99%
“…In addition, the role of parents is a key factor in modeling resilient responses to children and creating a resilience-rich environment. Some CWS may benefit from targeted support and build their own resilience to overcome the challenges about stuttering (19) .…”
Section: Studies On Resilience Social Support and Trait Anxiety Levelsmentioning
confidence: 99%
“…5 Simply, Smith and colleagues describe resilience as one's ability to bounce back. 6 Though there is a vast amount of literature regarding resilience in children exposed to stress, [7][8][9] there is less information available about adults, particularly older adults living with chronic illness. Hence, the purpose of this study was to fill this knowledge gap by evaluating the association between resilience and psychological outcomes for older adults living with chronic illness.…”
mentioning
confidence: 99%
“…Additionally, people with resilient mindset are able to regulate their emotions, thoughts and behaviors effectively, which help them to better adapt to stressors. Similar to the literature on resilience, some studies have emphasized the importance of developing a resilient mindset in order to effectively manage responses to stressors and achieve positive outcomes (Arewasikporn et al, 2019;Arslan & Coşkun, 2023;Caughter & Crofts, 2018;Hansen et al, 2021;Wong et al, 2021). For instance, Hansen et al (Hansen et al, 2021) found that individuals with lower levels of resilient mindset experienced worse physical and mental health, and higher levels of burnout and worry during the COVID-19 pandemic.…”
Section: Resilient Mindset and Mental Well-beingmentioning
confidence: 98%